Multidimensional Scaling as a Dialectometrical Technique - Embleton, Sheila (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1988)
Dialectometry is the study of quantitative measures of distance between dialects. Any dialectometrical technique must deal with three issues: how to construct a distance measure, what to do with the resulting numbers, and how to interpret the results. The first is relatively independent of the technique used and will not be discussed here; the second and third are intimately bound to the technique used. Two of several existing techniques involving maps (those of Séguy and Goebl) are presented as background. A new method, using maps produced by multidimensional scaling, is explained, showing how the traditional notion of isogloss bundle appears and how the maps are interpreted. The paper concludes with an exemplification of the technique on data from Orton and Wright 1974.